Preliminary Report on a Survey of Pre-Classical Remains in Southern Turkey - Mellaart, Jaraes
Introduction — South and South-West Coast of Anatolia from Mersin to the Maeander — Early Chalcolithic (or Neolithic) Material from the Beyşehir — Seydişehir Area — Chalcolithic Painted Pottery from the Konya Plain and the Calycadnus (Görsu) Valley ― Chalcolithic Pottery in the South-West of Anatolia — The Early Bronze Age — The Early Phase of the Early Bronze Age in the Konya Plain — South-West Anatolia.